Perspesktif Sosiologi Hukum Terhadap Fenomena Begging Digital Pada Platform Tiktok di Indonesia Berdasarkan Teori Hukum Sebagai Alat Rekayasa Sosial : Penelitian - Siska Saragih; Agusmidah, Agusmidah; Rosmalinda, Rosmalinda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The phenomenon of digital begging on the TikTok platform, the act of soliciting money or digital gifts through live streaming, has become a new socio-legal issue in Indonesia. This practice utilizes digital interactions to solicit donations by constructing emotional narratives and portraying difficult situations to garner sympathy. Although considered a form of social solidarity, this phenomenon also raises concerns regarding individual exploitation, the degradation of social values, and the misuse of technology. This study aims to analyze the perpetrators' motivations, public responses, and the social and legal impacts of this phenomenon. Using descriptive qualitative methods and a content analysis approach, this study collected data through video observation and literature review. The analysis focused on communication patterns, themes raised, and interactions between perpetrators and audiences. The results show that Digital Begging has received a variety of responses, ranging from support as a creative outlet to criticism as a form of exploitation that normalizes unproductive behavior, potential fraud, and public manipulation. From a sociological perspective, regulations related to this practice remain unclear, creating gaps in the supervision and protection of minors and the elderly. In conclusion, this phenomenon reflects changing social dynamics in the digital era.